Matrix Gla Protein Is Associated With Risk Factors for Atherosclerosis but not With Coronary Artery Calcification - O'Donnell, Christopher J. (2006)
OBJECTIVES: Atherosclerotic coronary artery calcification (CAC) is associated with increased coronary heart disease (CHD) risk. Matrix Gla protein (MGP) is an inhibitor of calcification in vivo. However, little is known regarding the distribution of circulating MGP and its associations with CHD risk factors or with CAC in humans. METHODS AND RESULTS: Serum MGP concentrations were determined in 2 independent populations of men and women free of clinically apparent cardiovascular disease: study A, n=316, mean age 58 years, and study B, n=452, mean age 68 years. CAC was determined by computed tomography. Mean MGP concentrations were 98.4 and 198 ng/mL in men, and 97.4 and 201 ng/mL in women, in study A and study B, respectively. In both cohorts, MGP levels were higher with increasing age. In age-adjusted analyses, there was an association of circulating MGP with increasing Framingham CHD risk score (in study A, P=0.003 in men and P=0.016 in women, respectively; in study B, a nonsignificant increase in men and P=0.05 in women, respectively). Significant associations of circulating MGP with high-density lipoprotein and other individual CHD risk factors were also noted in both cohorts. There were no consistent associations between MGP and CAC after adjustment for CHD risk score in the 2 cohorts. CONCLUSIONS: MGP is associated with individual CHD risk factors and the Framingham CHD risk score in men and women free of clinically apparent CHD. The relation of MGP with CAC deserves further study in larger populations.